Validity and reliability of the Farsi version of the ascertain dementia 8-item (AD8-F) informant interview in Iranian patients with mild neurocognitive disorder - Maryam Pourshams; James E. Galvin; Pouya Farokhnezhad Afshar; Pamela Gail Santos; Shahrzad Bazargan-Hejazi; Leila Kamalzadeh; Behnam Shariati; Seyed Kazem Malakouti (BMC Geriatrics, 2022)
Abstract Background For screening and distinguishing between mild neurocognitive disorder (mNCD) and normal cognitive age-related changes in primary care centers, a simple and practical tool is necessary. Therefore, this study aims to determine the validity and reliability of the Farsi version of the Ascertain Dementia 8-item (AD8-F) informant interview in patients with mNCD. Methods This is a study of the psychometric properties of the Farsi AD8. The participants include sixty informant-patient dyads with mNCD and sixty controls with normal cognition. The AD8 was compared to the mini-mental state examination (MMSE) and the Mini-Cog. As a gold standard, the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) criteria for mNCD was used. The reliability was measured using internal consistency and test-retest. Validity was assessed by evaluating the content, concurrent, and construct validity. Data were analyzed via Cronbach’s α, Pearson correlation, independent t-test, and analysis of variance (ANOVA) and area under the curve (AUC) by statistical package for the social sciences (SPSS) v.23. Results Cronbach’s α was 0.71. Test-retest reproducibility was 0.8. The AD8 had inverse correlations with the Mini-Cog (r = − 0.70, P < 0.01) and MMSE (r = − 0.56, P < 0.01). The area under the curve was 0.88. The optimal cutoff score was > 2. Sensitivity and specificity were 80 and 83%, respectively. The positive predictive value was 83%. The negative predictive value was 81%. Conclusion Our results suggest that this tool can be used as a screening tool to detect a mild neurocognitive disorder in primary care centers.